Build a webSocket-based chat backend in Go. (Manning Publications, 2022)
In this video Amit presents his liveProject series, in which he teaches how to use the Go programming language to build the backend for a customer support chat feature. The features of the Go programming language and its rich ecosystem allow you to create a highly scalable backend application out of the box.